Literature Review Benefits and Proposed Implementation of New Seven QC Tools in Testing Laboratories - Efendi, Riki; Purba, Humiras Hardi (Universitas Mercu Buana, 2024)
Monitoring laboratory testing competence and performance is a critical factor that requires constant attention. Timely corrective actions must be taken whenever non-conformities arise. This research investigates the benefits and proposed application of the New Seven QC Tools across various industries through a literature review. The articles were selected using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach from online databases such as Google Scholar, ResearchGate, Crossref, Semantic Scholar, and Scopus, focusing on publications between 2013 to 2024. 30 selected articles were analysed in terms of demographics (research objectives, results, country of origin, publication year, number of tools used, and sequence of tool usage at each step) and the benefits and proposed applications for testing laboratories. The analysis results indicate that the implementation of the New Seven QC Tools can be applied to identify and propose improvements for existing problems in testing laboratories, ultimately leading to enhanced test result quality.